Sustainable Supply Chain Management in the Book Publishing Sector - Díaz-Madroñero, Manuel; Mula, Josefa; Poler, Raúl (Brazilian Journal of Operations & Production Management, 2013)
In recent years, the term sustainability has been considered by the academic community in the management, logistics and supply management areas. The emerging concept of sustainable supply chain management tries to balance economic long-term benefit of the members of the supply chain, as well as the environmental and social decisions, in order to satisfy the interests of the individual members of a supply chain and their stakeholders. The aim of this paper is to analyze the current status of sustainable supply chain management and its application to the Book Publishing sector. For this purpose, a review process of selected papers applied to the Book Publishing sector is carried out, from which the main conclusion is that there are no references which consider in an integrated way all partners.